Advances in the Immune Regulatory Role of Non-Coding RNAs (miRNAs and lncRNAs) in Insect-Pathogen Interactions - Moure, Ulrich Aymard Ekomi; Tan, Tingshan; Sha, Lin; Lu, Xiaoqin; Shao, Zhi; Yang, Guang; Wang, Yi; Cui, Hongjuan (Frontiers in Immunology, 2022)
Insects are far the most abundant and diverse living organisms on earth and are frequently prone to microbial attacks. In other to counteract and overcome microbial invasions, insects have in an evolutionary way conserved and developed immune defense mechanisms such as Toll, immune deficiency (Imd), and JAK/STAT signaling pathways leading to the expression of antimicrobial peptides. These pathways have accessory immune effector mechanisms, such as phagocytosis, encapsulation, melanization, nodulation, RNAi-mediated virus destruction, lysis, autophagy, and apoptosis. However, pathogens evolved strategies that circumvent host immune response following infections, which may have helped insects further sophisticate their immune response mechanisms. The involvement of ncRNAs in insect immunity is undeniable, and several excellent studies or reviews have investigated and described their roles in various insects. However, the functional analyses of ncRNAs in insects upon pathogen attacks are not exhaustive as novel ncRNAs are being increasingly discovered in those organisms. This article gives an overview of the main insect signaling pathways activated by pathogen invaders and summarizes the latest findings of the immune modulation role of both insect- and pathogen-encoded ncRNAs, especially miRNAs and lncRNAs during insect-pathogen crosstalk.